Impact of CYP2C19 point-of-care testing on the clinical outcome in patients receiving personalized clopidogrel therapy: systemic review and meta-analysis - Mohammed, Shaban; Ali, Zainab; Mohammed, Nermin; El-Menyar, Ayman; Al Suwaidi, Jassim; Al-Hail, Moza; Al-Muftah, Wadha; Abdel-Latif, Rania; Sim, Maw Shin (Frontiers in Pharmacology, 2025)
ObjectiveEvidence on the utility of CYP2C19 point-of-care (POC) testing to guide antiplatelet therapy selection in patients with acute coronary syndrome (ACS) or stable coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) is currently limited. To address this gap, a meta-analysis was conducted to assess the clinical impact of CYP2C19 POC genotyping in ACS patients treated with P2Y12 inhibitors in PCI settings. The study compared clinical outcomes between standard care and genotype-guided antiplatelet therapy in ACS or CAD patients undergoing PCI, leveraging POC genotyping for rapid therapy optimization.MethodPubMed, EMBASE, Cochrane, Scopus and ProQuest. Central databases were searched up to 30 August 2025, for studies evaluating the use of point-of-care CYP2C19 genotyping to guide antiplatelet therapy in ACS/CAD patients undergoing PCI, comparing clinical efficacy and safety with conventional P2Y12 inhibitors. Two independent reviewers assessed study eligibility, extracted data, and evaluated the risk of bias. Risk ratios (RRs) with 95% confidence intervals were computed using random-effects models, with study heterogeneity assessed by the I2 index. The primary outcome included major adverse cardiovascular events including myocardial infarction, stroke, stent thrombosis or death and bleeding risk within 12 months of PCI.ResultsA total of four randomized controlled trials (RCTs) were included in the meta-analysis, comprising 5912 antiplatelet-treated ACS/CAD patients undergoing PCI. The analysis showed minimal statistical heterogeneity and low risk of bias. Compared with the standard treatment group, the genotype-guided group demonstrated a significantly lower risk of recurrent myocardial infarction (RR 0.54, 95% CI 0.38–0.77, P = 0.001). Although there were no significant differences in the efficacy outcomes for cardiovascular death, stroke, stent thrombosis, or bleeding complications, the calculated composite MACEs were significantly reduced in the genotype-guided group (RR 0.59, 95% CI 0.48–0.72, P = 0.001).ConclusionGenotype-guided antiplatelet therapy using CYP2C19 POC genotyping prior to PCI in ACS/CAD patients may reduce the risk of recurrent myocardial infarction and composite MACEs compared to standard treatment, highlighting the importance of POC genotyping for facilitating rapid and effective therapeutic decision-making.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251157778, identifier CRD420251157778.